Social Media in Building Relationships Between Companies and Representatives of Generation Z in the CRM Concept - Anna Korombel; Olga Lawinska (International Journal of Supply Chain Management, 2021)
Building social media relationships with Generation Z members is a huge challenge for today’s enterprises, not only because they are the least studied generation, but also because they represent different values than those of the previous generations. It is important that both sides of the relationship – the customer and the entrepreneur – are on social media at the same time and in the same place. This would enable communication and relationship building. The aim of the paper was to identify social networking portals, which are most often used by the representatives of Generation Z as an element of building relationships with companies. The study of Generation Z attitudes towards brands on social media is part of broader research conducted by the authors among students in Poland and Great Britain in 2020. The method used in the study was a survey, as part of which the CATI surveying technique was used. For analysis of the study material, descriptive statistics measures were used. Analysis of the collected empirical data provided the basis for verifying the research hypotheses. The findings show which social networking portals are most often used by respondents of Generation Z in customer-company relationships. Additionally, the strength of the relationships between the analysed variables and the respondent's gender and place of residence was verified.